Willie & Babs, Phil & Bob: “et moi, et moi, et moi…" (On Reading Pornography) - Stéphane Vanderhaeghe (Sillages Critiques)
Taking its cue from a broad definition of pornography in literature and building up on the ambiguous relationship uniting William Gass’s Willie Masters’ Lonesome Wife to its parodic response in Robert Coover’s “On Mrs. Willie Masters,” this article aims at interrogating the ways in which these texts, whose aesthetics verges on the pornographic, short-circuit the usual paths to meaning. If in both cases emphasis is put on the textual performance, the reader/critic sees herself beaten on her own turf and can only remark performatively, and give in to the evidence, that what these texts perform, overexposing them in the light of a writing given to simulation, are none other than her own critical obsessions.